USE OF INNOVATIVE METHODS IN TEACHING ENGLISH: 1-SON 3-TO’PLAM IYUL 2023 yil - TSUULL, senior student, Translation theory; practice faculty, Gulimboyeva Nozima Azimboy qizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
This article describes the use of modern methods in English language teaching, the goals and tasks of English language teaching, the linguistic aspects of the English language teaching methodology, the features of the English language background. The main factor of increasing the quality and efficiency of education is the use of modern and new innovative pedagogical technologies by our pedagogues today to educate mature specialists who have a high level of general professional culture, social activity, independent thinking, and the ability to solve their tasks without difficulty.